Use of medication in patients with mental disorders treated at a hospital in Roraima: a cross-sectional study - Soraya Kuyat VICENZI; Danielly Costa ROCHA; Carla Araújo BASTOS-TEIXEIRA; Letícia Silva AZEVEDO; Jackeline Costa MACIEL (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objectives: To analyze the profile of medications prescribed for patients with mental disorders treated at a hospital in Roraima. Methods: This is a descriptive, cross-sectional and quantitative study, collecting retrospective data from prescriptions and medical records of patients treated in the psychiatry unit of a hospital in Roraima from February 2018 to February 2020. The study was developed in accordance with with the recommendations of the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) statement for observational studies. For data analysis, it was the IBM Statistical Package for the Social Sciences 23.0 was used. The research was approved by the Research Ethics Committee under opinion 4,614,305. Results: A total of 156 patients were included in the research and the analysis of their medical records and prescriptions revealed that the majority of these patients were male (n = 88, 56.4%), aged between 30 and 39 years ( n = 51, 32.7%), mixed ethnicity (n = 136, 87.2%), single marital status (n = 76, 48.7%), diagnosed with 1 mental disorder (n = 119, 76.3%), classified within the Spectrum of Schizophrenia and Other Psychotic Disorders (n = 80, 51.3%). The prescriptions contained a total of 5 or more medications (n = 105, 67.3%), with 2 or more antipsychotics (n = 116, 74.4%), hospital stay length of 6 to 16 days (n = 61, 39.1%). With regard to prescribed drugs, the main classes were antipsychotics, anxiolytics and antiepileptics. The most frequent drugs were haloperidol (n = 110, 70.5%), promethazine (n = 97, 62.2%), levomepromazine (n = 85, 54.5%), diazepam (n = 83, 53.2%), clonazepam (n = 79, 50.6%), biperiden (n = 52, 33.3%), midazolam (n = 41, 26.3%), risperidone (n = 39, 25.0%), and lithium carbonate (n = 37, 23.7%). Conclusion: The presence of polypharmacy, the high frequency of drugs with the potential to produce adverse effects, highlights the need for greater care with the pharmacotherapy of patients with mental disorders, whether in acute or thermal treatment, increasing patient adherence, improving their quality of life.